Analisis Perbandingan Pengukuran Konsumsi Daya Motor BLDC 350W Melalui Pengukuran Dynamometer dan Pengujian On-road - Utomo, Satryo Budi; Hardianto, Triwahju; Arifin, Achmad Zainul (Jurnal Arus Elektro Indonesia, 2025)
Testing the overall performance of electric vehicles requires extensive on-road testing with varied conditions. Considering the amount of time and effort required for on-road testing, using a dynamometer as a testing tool can be an alternative. In this research, a dynamometer is modeled so that the load used is equivalent to the load on the urban car of the University of Jember. The purpose of this study is to analyze and validate the dynamometer in accordance with actual road testing conditions. The research was conducted by comparing power consumption measurements obtained from on-road testing with those obtained using a dynamometer. In each test, variations in PWM usage strategies were also applied to determine which PWM variations result in the most efficient power consumption. The study shows that the difference in power measurement results between the on-road testing method and the dynamometer method has a maximum difference of 7.58%. The resulting discrepancy is relatively small, leading to the conclusion that testing with the dynamometer method can represent direct testing. Another result obtained is that the variation of using constant PWM achieves the most efficient energy consumption.